PERANAN GURU DALAM MENGEMBANGKAN KOMPETENSI PEDAGOGIK UNTUK MENINGKATKAN DISIPLIN BELAJAR SISWA DI SD NEGERI TAMANSARI I - Meli Komara, - (2021)
The research raised the theme of the role of teachers in developing pedagogical competence to improve student learning discipline at SD Negeri Tamansari I. The theme was based on observations, interviews and documentation with principals, teachers, and students at SD Negeri Tamansari I who said that the role of teachers in developing Pedagogic competence is considered not yet competent so that it affects the learning discipline of students. In this study, the focus of the problem is how to describe the role of teachers in developing pedagogic competence in the aspects of mastering learning theory and learning principles, aspects of developing the potential of students, aspects of educational learning activities and how the disciplinary information data of SD Negeri Tamansari I students after receive learning. The purpose of this study was to describe the information data on the role of teachers in developing pedagogic competencies in the aspects of mastering learning theory and learning principles at SDN Tamansari I, to describe information data on the role of teachers in developing pedagogic competencies in the aspects of developing the potential of students at SDN Tamansari I , to describe the information data on the role of teachers in developing pedagogic competencies in the aspects of teaching learning activities at SDN Tamansari I, and to describe information data on student learning disciplines at SDN Tamansari I after receiving learning. The method used in this research is a descriptive analytical survey using a qualitative approach to the problems related to the role of the teacher in developing pedagogic competence and student learning discipline after receiving learning. The technique of collecting data by conducting field observations, interviewing respondents and documentation. This study succeeded in describing the role of teachers in developing pedagogical competencies to improve student learning discipline. Especially in the three pedagogical aspects, namely aspects of mastering learning theory and learning principles, aspects of developing the potential of students and aspects of educational learning activities. There is a change in learning discipline in a positive direction when the teacher can develop pedagogic competence in the aspects of mastering learning theory and principles and on the aspects of developing the potential of students. Where students can apply learning discipline when the teacher plays a full role during the learning process. However, there are unfavorable results regarding student learning discipline when the teacher's role is less able to develop pedagogic competence in the aspect of creating educational learning activities, where the learning process does not run optimally, is conducive and effective. Keywords: Role of Teachers, Pedagogic Competence, Student Learning Disciplin.